An Integrative Model for Soil Biogeochemistry and Methane Processes. II: Warming and Elevated CO2 Effects on Peatland CH4 Emissions. Issue 8 (10th August 2021) - Yuan, Fenghui; Wang, Yihui; Ricciuto, Daniel M.; Shi, Xiaoying; Yuan, Fengming; Hanson, Paul J.; Bridgham, Scott; Keller, Jason; Thornton, Peter E.; Xu, Xiaofeng
Abstract: Peatlands are one of the largest natural sources for atmospheric methane (CH4 ), a potent greenhouse gas. Climate warming and elevated atmospheric carbon dioxide (CO2 ) are two important environmental factors that have been confirmed to stimulate peatland CH4 emissions; however, the mechanisms underlying enhanced emissions remain elusive. A data‐model integration approach was applied to understand the CH4 processes in a northern temperate peatland under a gradient of warming and doubled atmospheric CO2 concentration. We found that warming and elevated CO2 stimulated CH4 emissions through different mechanisms. Warming initially stimulated but then suppressed vegetative productivity while stimulating soil organic matter (SOM) mineralization and dissolved organic carbon (DOC) fermentation, which led to higher acetate production and enhanced acetoclastic and hydrogenotrophic methanogenesis. Warming also enhanced surface CH4 emissions, which combined with warming‐caused decreases in CH4 solubility led to slightly lower dissolved CH4 concentrations through the soil profiles. Elevated CO2 enhanced ecosystem productivity and SOM mineralization, resulting in higher DOC and acetate concentrations. Higher DOC and acetate concentrations increased acetoclastic and hydrogenotrophic methanogenesis and led to higher dissolved CH4 concentrations and CH4 emissions. Both warming and elevated CO2 had minor impacts on CH4 oxidation. A meta‐analysis of warming and elevated CO2 impacts on carbon cycling in wetlands agreed well with a majority of the modeled mechanisms. This mechanistic understanding of the stimulating impacts of warming and elevated CO2 on peatland CH4 emissions enhances our predictability on the climate‐ecosystem feedback. Plain Language Summary: Peatlands are one of the largest natural sources for a potential greenhouse gas—methane. In this study, we took use of a number of field observational data to parameterize a microbial model before applying the model to understand the methane processes in a northern temperate peatland under a gradient of warming and doubled atmospheric carbon dioxide concentration. We found that warming and elevated carbon dioxide stimulated methane emissions through different mechanisms. Warming initially stimulated but then suppressed vegetative productivity while stimulating soil organic matter mineralization and dissolved organic carbon fermentation, which led to higher acetate production and enhanced methane production. Elevated carbon dioxide enhanced ecosystem productivity and soil organic carbon decomposition, resulting in higher dissolved organic carbon and acetate concentrations, which stimulate methane production. Both warming and elevated carbon dioxide had small impacts on methane oxidation. The modeling results are consistent with a global data synthesis. This mechanistic understanding of the stimulating impacts of warming and elevated carbon dioxide on peatland methane emissions enhances our ability to predict the interactions between the climate system and the terrestrial ecosystems. Key Points: Warming and elevated CO2 stimulate peatland CH4 emissions through different mechanisms The stimulating impact of warming is primarily through stimulation of microbial processes The stimulating impact of elevated CO2 is primarily through enhanced substrate availability by increased photosynthesis